The Impact of Active Learning Methods on Student Motivation and Academic Achievement in Elementary Schools - Yusof, Khairunnisa M.; Manza, Yuke (International Journal of Educational Insights and Innovations, 2024)
This study investigates the impact of active learning methods on student motivation and academic achievement in elementary schools. With a shift from traditional instructional approaches to more interactive and student-centered learning, this research employs a mixed-methods design, combining quantitative surveys and qualitative interviews. A structured survey was administered to 200 elementary students to assess their motivation levels and academic performance before and after the implementation of active learning strategies. Additionally, semi-structured interviews were conducted with 15 teachers to gain insights into their experiences with these methods. The findings reveal a significant increase in student motivation, with 75% of participants reporting enhanced engagement, alongside a 15% improvement in average test scores post-intervention. Qualitative data indicate that active learning fosters collaboration and communication skills among students, contributing to a richer classroom environment. Despite challenges related to training and resource availability, educators overwhelmingly support the integration of active learning techniques. This research highlights the effectiveness of active learning in promoting not only academic success but also essential soft skills, thereby advocating for its broader application in educational settings to create more engaging and productive learning experiences for young learners.